IMPLEMENTASI ALGORITMA RC4 STREAM CIPHER SEBAGAI METODE OBFUSCATION STRING PADA DATABASE MySQL - Muhammad Sholeh; Isnawaty Isnawaty; Bambang Pramono (Informatics Engineering Department of Halu Oleo University, 2019)
A database is a set of structured data and related to one another to form information. In the current technological development database management is very important considering the amount of information stored in the database of a system. One management that needs to be considered is the management of Database security.In securing the database there are many ways that can be used. One of them is by randomizing the contents of the database to confuse users who access the Database illegally. This randomization technique is called the Obfuscation String.One algorithm that can be used to randomize the database is the RC4 algorithm. This algorithm uses key lengths from 1 to 256 bits which are used to initialize tables as long as 256 bytes. This table is used to generate tables from a pseudo-random array using XOR operations with text to produce a ciphertext.The results of this study are a system that can randomize cell contents in a MySQL Database table using the RC4 Stream Cipher algorithm. From this study, it can also be concluded that the key length and the amount of data in the database table can affect the speed of program execution.Keywords—Database, Obfuscation String, RC4 AlgorithmDOI : 10.5281/zenodo.3066721